Pengembangan Sumber Daya Manusia Dalam Meningkatkan Mutu Pelayanan Di Lembaga Keuangan Syariah - Rohmah, Nafilatur (Al-Musthofa: Journal of Sharia Economics, 2018)
Costumer satisfaction is partly determined by the quality of service. Development of human resources in sharia financial institutions needs to be done in order to serve customers professionally. The development of sharia human resources is done with several strategies. The long term sharia human resource development strategy is done by involving external parties such as universities in the provision of professional sharia human resources. Meanwhile, short term strategy is done by applying sharia human resource developmenttechniques applied during staff work. The selection of appropriate strategies is done by adjusting the conditions and objevtives of the institution. Sharia human resource development strategies should be sustainable.